Advanced flip chip packaging - Lai, Yi-Shao; Tong, Ho-Ming; Wong, C. P. (Springer, 2013)
Advanced Flip Chip Packaging presents past, present and future advances and trends in areas such as substrate technology, material development, and assembly processes. Flip chip packaging is now in widespread use in computing, communications, consumer and automotive electronics, and the demand for flip chip technology is continuing to grow in order to meet the need for products that offer better performance, are smaller, and are environmentally sustainable. This book also:Offers broad-ranging chapters with a focus on IC-package-system integration.Provides viewpoints from leading industry executives and experts.Details state-of-the-art achievements in process technologies and scientific research.Presents a clear development history and touches on trends in the industry while also discussing up-to-date technology information.Advanced Flip Chip Packaging is an ideal book for engineers, researchers, and graduate students interested in the field of flip chip packaging